The future of ABPU agriculture: The 2nd MERCUSUR outlook - Jorge, Nicolás; Kanadani Campos, Silvia; Fonseca da Pereira, Vanessa; Vicentin Masaro, Jimena; Gianatiempo, Juan Pablo; Piñeiro, Valeria; Rava, Catalina; Costa, Ramiro (International Food Policy Research Institute, 2025)
In today’s complex and uncertain global environment, region-specific agricultural and trade outlooks are more essential than ever. While global projections from institutions such as the OECD-FAO and USDA provide valuable baselines, incorporating local perspectives is essential to capture the specific dynamics of emerging economies that are deeply integrated into international agrifood markets. Latin America and the Caribbean (LAC) is the world’s largest net food-exporting region, playing a central role in stabilizing supplies and reducing price volatility (IFPRI, 2025). Within LAC, Mercosur—Argentina, Brazil, Paraguay, and Uruguay (ABPU)—accounts for more than half of the region’s agrifood trade, concentrated in oilseeds, cereals, and animal proteins. Over the past two decades, agricultural exports from LAC have more than doubled, consolidating the region’s role as a net contributor to global food availability (Piñeiro et al, 2025a, 2025b). This performance highlights Mercosur’s structural weight in global markets, while also underscoring the climatic, institutional, and infrastructural challenges that call for tailored foresight tools.